Teaching effectiveness : motives, orientations and conceptions of teaching and learning in higher education - Jaafar, Haliza (2007)
Teaching effectiveness is important because effective teaching helps student learning. It has become even more important as the emphasis on quality in higher education has increased. Effective teaching does not occur by chance. Effective teachers have become good at what they do because they evaluate their practice.